Clinico-radiological profile of arrhythmogenic right ventricular dysplasia at a tertiary care center Two year experience - Shaheen, Feroze (Journal of the Saudi Heart Association, 2013)
BACKGROUND: Arrythmogenic right ventricular dysplasia (ARVD/C) refers to fibro fatty infiltration replacement of ventricular myocardium especially that of right ventricle. The clinical presentation varies from asymptomatic state to ventricular tachycardia, heart failure and even sudden death. Diagnosis is established using modified ARVD/C taskforce criteria. Among all the various modalities of diagnosis, magnetic resonance imaging (MRI) gives most comprehensive evaluation of both morphological and functional abnormalities in this disease. MRI may not only obviate need for myocardial biopsy but also give insights into the nature of disease like presence of left ventricular myocardial involvement. We present our 2 years experience of ARVD/C patents who were admitted in our center and in whom diagnosis of ARVD/C was supported by excellent MR imaging